DIFFERENCE IN TREATMENT OUTCOMES ACCORDING TO OPTICAL COHERENCE TOMOGRAPHY–BASED STAGES IN TYPE 3 NEOVASCULARIZATION (RETINAL ANGIOMATOUS PROLIFERATION). Issue 12 (December 2018) - Kim, Jae Hui; Chang, Young Suk; Kim, Jong Woo; Kim, Chul Gu; Lee, Dong Won; Cho, Soo Yeon
Abstract : Purpose: To compare 12-month treatment outcomes of Type 3 neovascularization among its different stages as classified using an optical coherence tomography–based method. Methods: This retrospective observational study included 40 patients (40 eyes) who were newly diagnosed with Type 3 neovascularization. The patients were initially administered 3 monthly anti–vascular endothelial growth factor injections. Repeat treatment was performed when recurrence of fluid was noted. Disease staging was classified using the optical coherence tomography–based method. The best-corrected visual acuity at diagnosis and at 12 months and degree of change in best-corrected visual acuity were compared among the different stages of the disease. In addition, incidence of progression in the disease stages was estimated. Results: Among the 40 patients, 14 (35.0%) were classified as Stage 2 and 26 (65.0%) were classified as Stage 3. The best-corrected visual acuity values at diagnosis and at 12 months were 0.61 ± 0.31 (20/81 Snellen equivalents) and 0.46 ± 0.30 (20/57) in the Stage 2 group and 0.67 ± 0.42 (20/93) and 0.70 ± 0.49 (20/100) in the Stage 3 group, respectively. There was a significant difference in best-corrected visual acuity change between the two groups (P = 0.036). During the follow-up period, 3 retinal pigment epithelium tears and 2 submacular hemorrhages had developed in the Stage 3 group. Progression of the disease from Stage 2 to Stage 3 was noted in 2 patients (14.3%). Conclusion: The visual outcome was worse in Stage 3 than in Stage 2, and adverse events that may lead to abrupt visual deterioration developed only in Stage 3. Further studies are needed to reveal whether anti–vascular endothelial growth factor therapy can suppress the progression of the disease stages. Abstract : The 12-month treatment outcome of anti–vascular endothelial growth factor for Type 3 neovascularization was significantly worse in Stage 3 than in Stage 2. Tear of the retinal pigment epithelium and submacular hemorrhage was noted only in Stage 3.